2008
DOI: 10.1089/ten.tea.2007.0347
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Interleukin-1 Response Between Engineered and Native Cartilage

Abstract: Unlike native cartilage explants that are used in autologous tissue transfer procedures, engineered cartilage constructs are typically highly fragile when first formed and must rely on cellular activity to develop over time. However, inflammatory cytokines such as interleukin-1alpha (IL-1alpha) are often present in target joints and may interfere with this development process. Herein we examine to what extent nascent engineered tissue is susceptible to chemical perturbations by IL-1alpha (10 ng/mL), especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 44 publications
8
67
1
Order By: Relevance
“…7D). The peak construct values achieved in this study were E Y , 743 kPa; GAG, 7.6%ww, G*, 2.8 MPa; and collagen, 6.2%ww, which compare favorably with native bovine wrist cartilage [30]. Histology showed a homogeneous extracellular matrix distribution (GAG and collagen) for constructs exposed to BG 13-93 on Days 28 to 42 (Fig.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…7D). The peak construct values achieved in this study were E Y , 743 kPa; GAG, 7.6%ww, G*, 2.8 MPa; and collagen, 6.2%ww, which compare favorably with native bovine wrist cartilage [30]. Histology showed a homogeneous extracellular matrix distribution (GAG and collagen) for constructs exposed to BG 13-93 on Days 28 to 42 (Fig.…”
Section: Resultssupporting
confidence: 51%
“…In Study 1, at Day 42, BG 13-93-containing constructs had a mean concentration of GAG in the chondrocyte-seeded agarose gel layer of 6.29%ww, which is comparable to native bovine cartilage [30] (Fig. 4A).…”
Section: Resultsmentioning
confidence: 74%
“…For instance, it has been shown that cultivating partially or fully mature engineered cartilage in vitro allows implanted tissue to withstand the harsh catabolic environment better than a freshly seeded or underdeveloped construct. 5,6 Other strategies include delivery of steroids, such as dexamethasone, or exogenous crosslinking factors. [6][7][8] However, biocompatible substances that sustainably scavenge radicals and protect de novo cartilage from an inflammatory response are more advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Other strategies include delivery of steroids, such as dexamethasone, or exogenous crosslinking factors. [6][7][8] However, biocompatible substances that sustainably scavenge radicals and protect de novo cartilage from an inflammatory response are more advantageous. In this study, we investigated the effect of cerum oxide nanoparticles in culture to act as a protectant for engineered cartilage against cytokine exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation